Bola em jogo entre Brasil e República Federal da Alemanha: cientificidade e modelagem pedagógica na formação de professores na Escola de Educação Física da UFMG (1963-1982) - Fernanda Cristina dos Santos (2017)
This study approaches a relation between Brazil and Federal Republic of Germany, between the 1960s and 1980s, regarding the process of constitution of a teaching model and a scientificity for the formation of Physical Education teachers, more specifically in the School Of Physical Education of the Federal University of Minas Gerais (EEF-UFMG). The objective was to understand the contributions of German practices, subjects and institutions to the conformation of a scientific and pedagogical thought for the Brazilian Physical Education in the decades studied. This exchange was made possible through cultural and technical-scientific agreements proposed in view of the need for both nations to expand their international policies. In the search of past vestiges, the Center for Memory of Physical Education, Sports and Leisure (Cemef / UFMG) was a privileged place for research work. In it were examined didactic materials among them films and class programs documents related to postgraduate courses, educational campaigns, newsletters, correspondence and works by German authors of the Coleção Educação Física, from the publishing company Ao Livro Técnico. Moreover, as a leading source for this research, was used the report produced by the German teacher Listelotte Diem called Sportförderung in Brasilien: Berich 9uber die Förderung des Sports in der Föderativen Republik Brasilien durch die Bundesrepublik Deutschland 1963 bis 1982, which deals with the promotion of Sport, in Brazil, between the years mentioned. Beyond the sources located in the Cemef / UFMG collection, interviews were conducted with teachers from the EEF-UFMG who participated directly in different movements promoted by the german-brazilian agreement. The mobilization of this documentary set allowed us to understand the dynamics of this marked German presence in the School and also in projects carried out by the city hall of Minas Gerais. In this sense, it can be said that the propositions brought by the teachers of the European country were configured as important contribution to the pedagogical and scientific practices constituted in that institution, especially from the end of the 1970s. It was also possible to understand that the pedagogical modeling that was designed and gaining legitimacy in the EEF-UFMG, from a broad spectrum of German contributions, was mainly related to a way of teaching anchored in a systematized scientific production, with valuation of the experimentation tolls, measurement and scanning of the motor gesture and the physical capacities, that emphasized the sports training. It can be said that this movement produced a kind of new rootedness in the way in which this School and the formation of its teachers started to operate especially from the end of the 1980s.